RESPON PEMBERIAN LIMBAH KELAPA SAWIT (Solid) TERHADAP TANAH MARGINAL DENGAN INDIKATOR TANAMAN BAYAM (Amaranthus tricolor L.) - Dona J Nadeak; Karamoy Lientje Th; Wiesje J.N. Kumolontang (Universitas Sam Ratulangi, 2021)
ABSTRACTThe response of spinach as an indicator. (Amaranthus tricolor L.) grown on marginal soil givenpalm oil waste (solid) is the aim of this study. A completely randomized design (CRD) consistingof four treatments i.e., P0 (Control), P1 10 tons/ha, P2 20 tons/ha, P3 30 tons/ha in threereplicates were used during three month trials. The observed variables were plant height,number of leaves, and fresh weight of spinach plants.The results showed that the need forappropriate technology application of plam oil solid waste and its soil management systems onmarginal soils can improved the performance of the grown spinachs on this soil. The applicationof palm oil waste (solid) has a significant effect on the growth of spinach plants in terms of plantheight and number of leaves at the age of 3 WAP (Week After Planting) and of 4 WAP.Treatment of 20 tons of oil palm solid per ha gave the highest yield on plant height and numberof leaves. Furthermore, the fresh weight of spinach plants given 30 tons of oil palm solid per hagave the heaviest weight at 4 WAP.Key words : marginal soils, palm oil waste (solid), spinach plants